Analytical theory of the spin-orbit state of a binary asteroid deflected by a kinetic impactor - Gaitanas, Michalis; Efthymiopoulos, Christos; Gkolias, Ioannis; Voyatzis, George; Tsiganis, Kleomenis (Celestial mechanics and dynamical astronomy, 2024)
We study the perturbed-from-synchronous librational state of a double asteroid, modeled by the Full Two Rigid Body Problem (F2RBP), with primary emphasis on deriving analytical formulas which describe the system’s evolution after deflection by a kinetic impactor. To this end, both linear and nonlinear (canonical) theories are developed. We make the simplifying approximations (to be relaxed in a forthcoming paper) of planar binary orbit and axisymmetric shape of the primary body. To study the effect of a DART-like hit on the secondary body, the momentum transfer enhancement parameter β is introduced and retained as a symbolic variable throughout all formulas derived, either by linear or nonlinear theory. Our approach can be of use in the context of the analysis of the post-impact data from kinetic impactor missions, by providing a precise modeling of the impactor’s effect on the seconadry’s librational state as a function of β .